A view of optical soliton solution of the coupled Schrödinger equation with a different approach - Ozkan, Ayten; Ozdemir, Nagehan; Ozkan, Erdogan Mehmet (IOP Publishing Ltd, 2024)
The goal of this study is to investigate to optical soliton solution of the nonlinear coupled space-time Schr & ouml;dinger equation using the Beta derivative and Sine-Gordon Expansion Method. All calculations in this study are made using some software program and the solutions obtained are substituted in the equations. New soliton solutions have been found using the suggested method for solving these problems. The solutions obtained have important areas of use in the fields of mathematical physics, in the field of quantum physics, optic and engineering.
Keywords: beta derivative; Sine-Gordon expansion method; soliton solution; TRAVELING-WAVE SOLUTIONS; Physics